Optimization of Biological Substance Production from Bacillus subtilis Strain OK1101 in A 10 L Stirred Fermenter - Promma, Nantanath; Yeesin, Ponlkrit; Saeng-ngam, Sukhumaporn; Krajangsang, Sukhumaporn (Srinakharinwirot University Journal of Sciences and Technology, 2025)
Bacillus subtilis strain OK1101, isolated from soil, has been reported to produce amylase and cellulase enzymes and exhibits potential for inhibiting weedy rice germination by more than 50% at the flask scale. This study aimed to determine optimal conditions and develop a biocontrol formulation from B. subtilis OK1101 for managing weedy rice in paddy fields. The effects of medium composition and physical parameters were investigated using a 10 L bioreactor. Among the tested media, formulation T supported the highest growth and biomass production, yielding 3.01±0.19 g/L, with viable cell counts of 7.91±0.02 log CFU/ml and an optical density at 600 nm of 2.28±0.11. Furthermore, cultivation at an agitation speed of 200 rpm combined with an aeration rate of 0.07 vvm (volume of air per volume of medium per minute) was found to be optimal for microbial cell production. Under these conditions, the maximum biomass yield reached 11.97±0.76 g/L, with viable cell counts of 8.93±0.17 log CFU/ml and optical density at 600 nm of 0.64±0.13. These findings demonstrate that B. subtilis OK1101 can be efficiently cultivated under controlled bioreactor conditions, achieving enhanced production of biomass, enzymes, and biological substance when using an aeration rate of 0.07 vvm and agitation speed of 200 rpm.